Culture in Transition: Problems of Thinking and Speech Development - Dudina, M (KnE Life Sciences, 2018)
The authors consider this psychological and pedagogical research to be relevant as it advances the discussion of Lev Vygotsky and Alexander Luria’s cultural–historical theory of higher psychological functions and seeks to understand environment as a source of psychological development rather than as a condition for it. The interiorization of contemporary cultural phenomena bears the signs of fragmentary, mosaic thinking that makes it difficult to nurture the ability to analyze and identify cause-and-effect relationships. A superficial approach to the ever-expanding volume of knowledge prevents one from comprehending concepts, which has a negative impact on the development of consciousness, cognitive and affective functions, activity, verbal and non-verbal communication, and of the conceptual structure of the world and self-reflection on one’s place in the world. Speech enriches and stimulates thinking, thus driving the educational process toward a search for ways of integrating innovative tools and methods of engaging learners in adequate types of learning activities in the ‘the zone of proximal development’. The author’s many years of experience confirms the psychological and pedagogical effectiveness of the acquisition of meta-disciplinary content in philosophical propaedeutic starting from primary school. Meta-disciplinarity as a universal integratory phenomenon encompasses meta-knowledge, meta-tools, meta-skills, and meta-action that are connected with mental activity in super-subject knowledge acquisition by contrast with subject knowledge acquisition. Philosophical knowledge as meta-knowledge has a high degree of generalization and facilitates a holistic view of the world and the human’s place in it that is registered in the speech of the linguistic persona. The latter grows from being ‘knowledgeable’ to being a ‘thinking’ and ‘creating’ one. The theoretical and practical novelty of the study is that explores the concept of self-care in education. Keywords: digital civilization, changing society, culture, linguistic persona, higher psychological functions, thinking and speech, mosaic thinking, ‘self-care’